The Rotary Fluidized BioFilm Media with Improved Fluidity and Reaction Efficiency - HAN, SANG BAE (2018)
According to the present invention, a fluidized biofilm support comprises: an outer support having a plurality of through-holes and a space while microbes proliferate by being attached; a microbial contact material having a specific surface area and a large porosity in which microbes proliferate by being attached while having a penetrable flow path; and a blade and a rotation unit capable of converting the flow of a fluid into a rotational force. The blade and the rotation unit act as a structural material and a biofilm support, and rotate the biofilm support by functioning as an aberration for converting flow energy of the fluid into rotational force. The biofilm support includes one of the following functions: contact enhancing functions for increasing the contact frequency between microorganisms and contaminants; entangling prevention functions for preventing entangling between the biofilm supports; microbubble and scum detachment functions for preventing attachment of microbubbles and scum; and scum layer disturbance functions for disturbing scum layers stacked on a water side. 본 발명에 따른 유동상 생물막 담체는, 다수개의 관통구 및 공간부가 구비되며 미생물이 부착증식하는 외곽 담체와, 관통유로가 구비되며 미생물이 부착증식하는 비표면적과 공극율이 큰 형상의 미생물 접촉재와, 유체의 유동을 회전력으로 전환할 수 있는 블레이드와 회전수단을 포함하고, 상기 블레이드 및 회전수단은 구조재와 생물막담체로 작용하는 한편, 유체의 유동에너지를 회전력으로 전환하는 수차로 작동하여 생물막담체를 회전시키므로 상기 생물막담체는 미생물과 오염물질의 접촉 빈도를 증대시키는 접촉증대 작용과, 생물막담체들이 서로 엉키는 것을 방지하는 엉킴방지 작용과, 미세기포 및 스컴의 부착을 방지하는 미세기포 및 스컴의 탈리 작용과, 수면측에 적층되는 스컴층을 교란시키는 스컴층 교란 작용 중에서 어느 하나 이상의 작용을 할 수 있는 것을 특징으로 한다.